Adjuvant Radiation in Older Patients With Glioblastoma: A Retrospective Single Institution Analysis - Lee, Jessica W.; Kirkpatrick, John P.; McSherry, Frances; Herndon, James E.; Lipp, Eric S.; Desjardins, Annick; Randazzo, Dina M.; Friedman, Henry S.; Ashley, David M.; Peters, Katherine B.; Johnson, Margaret O. (Frontiers in Oncology, 2021)
Objectives: Standard 6-week and hypofractionated 3-week courses of adjuvant radiation therapy (RT) are both options for older patients with glioblastoma (GBM), but deciding the optimal regimen can be challenging. This analysis explores clinical factors associated with selection of RT course, completion of RT, and outcomes following RT. Materials and Methods: This IRB-approved retrospective analysis identified patients ≥70 years old with GBM who initiated adjuvant RT at our institution between 2004-2016. We identified factors associated with standard or hypofractionated RT using the Cochran-Armitage trend test, estimated time-to-event endpoints using the Kaplan-Meier method, and found predictors of overall survival (OS) using Cox proportional hazards models. Results: 62 patients with a median age of 74 (range 70-90) initiated adjuvant RT, with 43 (69%) receiving standard RT and 19 (31%) receiving hypofractionated RT. Selection of short-course RT was associated with older age (p=0.04) and poor KPS (p=0.03). Eight (13%) patients did not complete RT, primarily for hospice care due to worsening symptoms. After a median follow-up of 37 months, median OS was 12.3 months (95% CI 9.0-15.1). Increased age (p<0.05), poor KPS (p<0.0001), lack of MGMT methylation (p<0.05), and lack of RT completion (p<0.0001) were associated with worse OS on multivariate analysis. In this small cohort, GTV size and receipt of standard or hypofractionated RT were not associated with OS. Conclusions: In this cohort of older patients with GBM, age and KPS was associated with selection of short-course or standard RT. These regimens had similar OS, though a subset of patients experienced worsening symptoms during RT and discontinued treatment. Further investigation into predictors of RT completion and survival may help guide adjuvant therapies and supportive care for older patients.